Unexpected Optical Blue Shift in Large Colloidal Quantum Dots by Anionic Migration and Exchange - Acebrón, María (2018)
Compositional changes taking place during the synthesis of alloyed CdSeZnS nanocrystals (NCs) allow shifting of the optical features to higher energy as the NCs grow. Under certain synthetic conditions, the effect of those changes on the surface/interface chemistry competes with and dominates over the conventional quantum confinement effect in growing NCs. These changes, identified by means of complementary advanced spectroscopic techniques such as XPS (X-ray photoelectron spectroscopy) and XAS (X-ray absorption spectroscopy), are understood in the frame of an ion migration and exchange mechanism taking place during the synthesis. Control over the synthetic routes during NC growth represents an alternative tool to tune the optical properties of colloidal quantum dots, broadening the versatility of the wet chemical methods.